Access and use of credit among households in the coastal Barangays in Miagao, Iloilo - Pagapulan, Sharlene Grace Bayogos
Credit is an important tool in financing the needs of individuals especially the poor and vulnerable individuals in the society. This study examined the access and use of credit among households in the coastal barangays in Miagao, Iloilo. The socio-economic conditions of households, beliefs awareness and participation to credit were described and the factors affecting the access and use of credit were determined. An interview schedule was used to collect information from 213 randomly selected household representatives from 22 coastal barangays in Miagao. A logistic regression model was used to determine the significant factors affecting access to credit. Result show that most of the study p0articipants with need for credit able to access credit during six months prior to interview (98%). The majority of them borrowed money from relatives, friends and neighbors (57%). Credit among the study participants were mostly utilized for education. Civil status, number of known credit sources, and travel time were the significant factors affecting access to credit at 1% level of significance. Information dissemination on credit sources availability in the local area and locating credit sources near the people are recommended.